Glycemic control in diabetic patients treated with Sitagliptin in a single tertiary centre - WS, Wan Juani; M., Azura Dina; S., Norlela; M., Norlaila; AW, Norasyikin; O, Ahmad Marzuki; R, Subashini; Loh, Huai Heng; Shahar, Mohammad Arif; O, Mohd Rahman; K., Nor Azmi (Malaysian Endocrine and Metabolic Society, 2014)
Background Sitagliptin is a DPP-IV inhibitor and has been proven to reduce HbA1c by 0.8% when used as monotherapy and up to 2.1% when used in combination with maximum dose of metformin. Objectives To evaluate the glycemic control in patients treated with sitagliptin either as monotherapy or as add on therapy. Design and Method This was a retrospective descriptive cross sectional study conducted from January 2014 till April 2014 involving type 2 diabetec patients treated with sitagliptin in UKMMC. Data were retrieved from electronic medical record and their fasting blood sugar and HbA1c at initiation of treatment and the following visit were analyzed. Results A total of 212 patients received Sitagliptin in our centre. Median duration of follow-up after initiation of Sitaglitin is 5.8 months (2.2,9.1). The median overall FBS at initiation of therapy was 8.4mmol/l (7, 10.1) and at follow up was 8mmol/l (6.2, 9.4) (p <0.05). The mean overall HbA1c at initiation of therapy was 8.2% (7.4, 9.2) and at follow up was 7.5% (6.8, 8.4) (p < 0.01). Eight (3.8%) patients received Sitagliptin as monotherapy, 51 (24%) received as dual oral therapy, 91 (42.9%) as triple oral therapy and 6 (2.8%) as fourth oral agents. Twenty-six (12.3%) received Sitagliptin in combination with other oral agents with basal insulin, 19 (9%) in combination with or without metformin and premixed insulin, 11 (5.2%) in combination with or without metformin and basal bolus insulin. The mean HbA1c at pre and post therapy, for those on monotherapy were 7.2% and 6.8% (p=0.205) respectively; dual oral therapy were 7.5% and 6.9% ( p =0.017), triple oral therapy 8.0% and 7.4% (p=0.001), quadruple oral therapy 8.3% and 7.6% (p=0.069), in combination with basal insulin 8.8% and 8.0% (p=0.045) , in combination with premixed insulin 9.9% and 8.2% (p=0.001), and in combination with basal bolus insulin was 9.1% and 8.8% (p=0.05) . Conclusions Significant HbA1c reductions were seen when Sitagliptin was given as dual or triple oral therapy with greatest reduction observed when it was added to premixed insulin treatment.